FAKTOR PENGARUH TERHADAP MINAT PEMBELIAN TIKET KM. DHARMA RUCITRA I RUTE BANJARMASIN-SURABAYA - Adenanthera Lesmana Dewa; Muhamad Thoriq Ramadani; Retno Mulatsih (Journal Of Business, Finance, and Economics (JBFE), 2023)
The purpose of this study was to find out whether the factors of service quality, waiting time, price rates, and facilities affect passenger interest in PT. Main Ocean Dharma. The sample in this study amounted to 100 passengers on the dharma rucitra I ship. Incidental Data Sampling Techniques. Data analysis used in this study was descriptive analysis and quantitative analysis, data were analyzed using multiple linear regression analysis with the help of (software) Statistical Package For Social Science (SPSS) version 26. The results of the research by testing the hypothesis t-test partially showed that service quality, waiting time, price rates, and facilities have a positive and significant effect on Passenger Interest in PT. Main Lutan Dharma. Based on the research results, it can be seen that the research model of the multiple linear regression equation is Y = -0.835 + 0.278X1 + 0.232X2 + 0.298X3 + 0.249X4 + µ. From the regression equation, it can be seen that the most dominant variable influencing passenger interest is the service quality variable with a regression coefficient of 0.298. And the R2 test (Adjusted R Square) yields a result of 0.562 or 0.56.2%, which means that Passenger Interest is influenced by the variables Waiting Time, Facilities, Service Quality, and Price Rates, which are 56% and other factors that affect User Interest by 44%.